Substrate integrate waveguide and microstrip antennas at 28 GHz - Yaqdhan Mahmood Hussein; Mohamad Kamal A. Rahim; Noor Asniza Murad; Mustafa Mohammed Jawad; Hatem O. Hanoosh; Huda A. Majid; Hussam H. A. Keriee (Institute of Advanced Engineering and Science, 2020)
In this paper, two antennas are designed using substrate integrated waveguide (SIW) and microstrip technology at 28 GHz. Parametric study for both antennas is presented to demonstrate the performance at millimeter wave frequency for wireless communication network (5G application). Roger RT5880 substrates with permittivity 2.2 and loss tangent 0.0009 are used to implement the antennas with two thicknesses of 0.508 mm and 0.127 mm respectively. Both antennas have the same size of substrate 12x12 mm with a full ground plane was used. Structures designs have been done by using computer simulation technology (CST). The simulation results showed that the antenna with SIW and roger RT 5880 substrate thickness 0.508 has better performance in term of return loss and radiation pattern than the microstrip patch antenna at 28 GHz. A return loss more than -10 dB and the gain are 6.4 dB obtained with wide bandwidth range of (27.4-28.7) GHz. This proving to increase the realized gain by implementing SIW at millimeter wave band for 5G application network.